Simplest would seem (5! + 4) x .5 = 62
and (5/5) x (5! + 4) x .5 = 62 to use all 5 numbers up.
(b) [5 x (5 + 5)] + (.5 x 4!) = 50 + 12 = 62
I am using .5... to mean ,5 recurring, below
(c) 55 - sqrt (4) + 5/.5,,, = 55 - 2 + 9 = 62
2007-01-05 18:35:39
·
answer #1
·
answered by Anonymous
·
1⤊
1⤋
(5x5) + 5 + (sqrt(4))^5
25 + 5 + 32 = 62
2007-01-05 03:20:10
·
answer #2
·
answered by MamaMia © 7
·
0⤊
0⤋
(5^4 - 5) / (5 + 5)
As follows:
5^4 = 625
- 5 = 620
/ 10 = 62
Edit: I was *so* close to being first... in that case let me give you a *bonus* way:
(5! * 5 ) / (5 + 5) + sqrt(4)
5! = 120
* 5 = 600
/ 10 = 60
+ sqrt(4) = 62
And a *bonus, bonus* way:
5! / sqrt(4) + (5+5) / 5
5! = 120
/ sqrt(4) = 60
+ 10/5 = 62
2007-01-05 03:18:26
·
answer #3
·
answered by Puzzling 7
·
2⤊
0⤋
well i dont know how big of a loser it makes me because i actually sat down and thought about and did a lot of math. because i am that bored. but here it goes
5^4=625
625/(5+5)=62.5
62.5-.5=62
one 4 is used, and four 5s are used (the last one is behind a decimal).
2007-01-05 03:31:55
·
answer #4
·
answered by Kyle W 1
·
0⤊
0⤋
(5^4-5)/(5+5)
2007-01-05 03:27:50
·
answer #5
·
answered by Dror 1
·
0⤊
0⤋
i know :)
(5^4 - 5)/ (5+5)
2007-01-05 03:17:04
·
answer #6
·
answered by iam_Amie 2
·
2⤊
0⤋